The Role Of Educators In Student Character Development With The Habituation Of Dzuhur Prayers In Congregtion - Rabiatul Adawiyah (Departement of Mathematics Education, 2023)
This research is an attempt to find out the results and activities of the congregational Asr prayer at the Rahmat Islmiyah Foundation school in Medan in building religious character so that a personal habit occurs in students with guidance from the role of the teacher figure as (1). Educators, (2) Teachers, (3) Facilitators, (4) Supervisors, (5) Servants, (6) Designers, (7) Managers, (8) Innovators, and (9) Assessors. This study uses a qualitative descriptive approach (qualitative research) in the form of interviews, word descriptions and documentation, so that it can answer all of the formulation of the problem.